The ethics of soil conservation in India - LAL, RATTAN (Journal of Soil and Water Conservation, 2018)
Soil, the most basic of all natural resources, is finite, unequally distributed among geographical regions, and prone to degradation by inappropriate land use and management practices. Therefore, the importance of sustainable management of land resources is rightfully emphasized in scriptures of all major religions. By taking the soil resources for granted and ignoring these teachings, humanity has paid a heavy price. Degradation of soil has in turn caused decline in productivity and led to the demise and extinction of once thriving civilizations such as that of the Mohenjo-Daro and Harappa. Whereas the basic principles of conserving and restoring soil resources have been known for millennia, there is a strong need to translate these principles into action. Involving community in soil conservation programmes, enhancing awareness about the importance of soil through education in primary and secondary schools, and involving religious organizations to preach the importance of soil may reverse the degradation trends. Realizing the importance of ethics and stewardship of soil resources is essential to both human wellbeing and nature conservancy.